The significance of the percentage of the defect size in spina bifida cystica in determination of the surgical technique - Ozveren, MF; Erol, FS; Topsakal, C; Tiftikci, MT; Akdemir, I (Springer-Verlag, 2002)
Aim: Our aim was to classify meningoceles and meningomyeloceles in terms of defect area as a percentage of the thoracolumbar region to make it possible to select the surgical technique accordingly. Materials and methods: Thirty-two cases were included in the study program. Any defect smaller than 8% of the thoracolumbar region was primarily sutured and classed as grade 1. Results: The defects that it was not possible to handle with primary suture because of the broad base and thereby closed with muscle-skin flaps were those occupying more than 8% of the thoracolumbar region and these were classed as grade 2. It was not possible to perform primary repair of any defect occupying more than 8% of the thoracolumbar area. Conclusion: The use of combined latissimus dorsi+gluteus maximus muscle-skin flaps was found to be safe in broad-based meningomyelocele defects, as they provide wider closures and permanent bolstering of the meningomyelocele defect, thus protecting the region against multiple trauma.
Keywords: defect percentage; meningocele; muscle-skin flap; meningomyelocele